Perceptions of a Dignified Death Among Elderly Veterans Using Homecare in South Korea. Issue 3 (August 2019) - Park, Sun A.; Lim, Ji Young; Yoon, Young Mi
This study was conducted to investigate perceptions of a dignified death among elderly veterans using homecare in South Korea. This study was a descriptive survey. The subjects were 161 elderly veterans using the homecare service of a national veterans' hospital for 1 year or more. Participants' demographic, illness, and care characteristics and perceptions of a dignified death were analyzed using descriptive statistics, t test, and analysis of variance (ANOVA). Participants' mean dignified death perception level was 3.18 on a 4-point Likert-type scale. Participants who received medical services free of charge had higher perceptions of a dignified death than those who had to pay. Having at least a college education, having above-average economic status, and being cared for by spouses or professionals were associated with higher perceptions of a dignified death. Participants' perception of a dignified death differed by socioeconomic factors rather than disease characteristics. Therefore, to improve perceptions of a dignified death among elderly veterans using homecare services, it might be necessary for the state to assume greater responsibility for their medical expenses, to build better community-based end-of-life care systems, and to promote health and welfare policies for dignified death–oriented social infrastructure.